2014
DOI: 10.1007/s00425-014-2098-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an apple TT2-type R2R3 MYB transcription factor functionally similar to the poplar proanthocyanidin regulator PtMYB134

Abstract: The apple MdMYB9 gene encodes a positive regulator of proanthocyanidin synthesis that activates anthocyanidin reductase promoters from apple and poplar via interaction with basic helix-loop-helix proteins. The regulation of proanthocyanidins (PAs, condensed tannins) is of great importance in food plants due to the many benefits of PAs in the human diet. Two candidate flavonoid MYB regulators, MdMYB9 and MdMYB11, were cloned from apple (Malus × domestica) based on their similarity to known MYB PA regulators. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 71 publications
1
60
0
Order By: Relevance
“…MYB134 and a GL3-like bHLH cofactor (bHLH079; see below) were not affected by MYB182 overexpression. However, MYB115, the MYBPA1-type positive PA regulator, and bHLH131, a PA synthesis cofactor of the TT8/DEL/ JAF13 group (Gesell et al, 2014), were affected in the MYB182-overexpressing hairy roots, and both showed reduced expression (Fig. 2D).…”
Section: Poplar Hairy Roots Overexpressing Myb182 Show Reduced Pa Levmentioning
confidence: 99%
See 4 more Smart Citations
“…MYB134 and a GL3-like bHLH cofactor (bHLH079; see below) were not affected by MYB182 overexpression. However, MYB115, the MYBPA1-type positive PA regulator, and bHLH131, a PA synthesis cofactor of the TT8/DEL/ JAF13 group (Gesell et al, 2014), were affected in the MYB182-overexpressing hairy roots, and both showed reduced expression (Fig. 2D).…”
Section: Poplar Hairy Roots Overexpressing Myb182 Show Reduced Pa Levmentioning
confidence: 99%
“…We had shown previously that the poplar ANR1 promoter is activated by MYB134 when cotransformed with the poplar bHLH131 cofactor into a transient expression system (Zifkin et al, 2012;Gesell et al, 2014). To show negative regulation by MYB182, a positive regulator such as MYB134 was used in combination with the MYB182 repressor construct, and the reduction in activation was measured.…”
Section: Myb182 Inhibits the Transactivation Of A Pa Promoter By Posimentioning
confidence: 99%
See 3 more Smart Citations